Understanding Diversity Ideologies From the Target's Perspective: A Review and Future Directions - Gündemir, Seval; Martin, Ashley E.; Homan, Astrid C. (Frontiers in Psychology, 2019)
We present a review of the diversity ideologies literature from the target’s perspective. In particular, we focus on how diversity ideologies—beliefs or organizational practices with regards to how to approach diversity—affect racial minorities’ and women’s self-perceptions and experiences at work. This review suggests that a diversity aware ideology (i.e., multiculturalism) is more beneficial than a diversity blind ideology (i.e., colorblindness) for racial-ethnic minorities (e.g., better performance outcomes; more psychological engagement, inclusion, and workplace satisfaction; more positive leadership self-perceptions; and reduced perceptions of bias and turnover intentions). In contrast, for women, gender-blindness is associated with more positive outcomes than gender awareness (e.g., enhanced self-confidence, pro-active behaviors and leadership emergence). Importantly, multiculturalism and gender-blindness can both produce negative side effects for racial minorities and women, respectively, which highlights the importance of developing approaches to address the shortcomings of these conventional ideologies. We discuss the implications and offer recommendations for future research.